Belas kasih diri (self compassion) pada mahasiswa - Fahada Bagas Karinda (Fakultas Psikologi, 2020)
Academic demands, adaptation, and socialization were things that must be experienced by every student. Going by these demands made students have unstable emotions. Prolonged negative emotions with no resolution made difficult for students to develop themselves and tend to withdraw from the environment. To overcome negative emotions, an individual must be able to accept all the realities, weaknesses, and problems that occur, this term refers to self compassion. Self compassion is a compassionate attitude or behavior towards ourself when facing difficulties, to accept all suffer, self-deprivation, and every failure as part of life. The purpose of this study was to determine general description of self compassion in students. Subjects were 345 students of University of Muhammadiyah Malang. Convenience sampling was used as sampling technique with Self Compassion Scale as measuring instrument. The results of this study were analyzed using quantitative descriptive test and showed that level of self compassion of students based on gender had a slight difference, 52,7% of men as well as 53,6% of women both in high category.